2013
DOI: 10.4081/ijas.2013.e65
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometrical Evaluation of Gastrointestinal Tract and Performance of Ross Broilers Hatched from Eggs Inoculated withSalmonellaEnteritidis Phage Type 4

Abstract: An experiment was carried out with 128 Ross chicks to evaluate the effects of Salmonella Enteritidis phage type 4 inoculated in eggs (contamination site vs inoculum), observing the site of inoculation by injection in allantoidal cavity or by shell direct contact and the combination with presence or absence of Salmonella Enteritidis phage type 4. Chicks were distributed in a completely randomised 2x2 factorial design (contamination site and inoculum). We evaluated the frequency of infected chicks, the morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(15 reference statements)
1
0
0
1
Order By: Relevance
“…In our present study, S. Enteritidis infection led to a significant decrease in villus height and a significant increase in crypt depth such that the VH:CD was reduced in the broilers infected with Salmonella. Similarly, previous reports showed that the VH:CD in the small intestine significantly reduced upon Salmonella infection (Andrade et al, 2013; Jazi et al, 2018;Wu et al, 2020). This outcome may be the result of Salmonella damaging the intestinal mucosa, affecting the absorption of nutrients, weakening the body's resistance, and then aggravating the intestinal mucosa.…”
Section: Discussionsupporting
confidence: 65%
“…In our present study, S. Enteritidis infection led to a significant decrease in villus height and a significant increase in crypt depth such that the VH:CD was reduced in the broilers infected with Salmonella. Similarly, previous reports showed that the VH:CD in the small intestine significantly reduced upon Salmonella infection (Andrade et al, 2013; Jazi et al, 2018;Wu et al, 2020). This outcome may be the result of Salmonella damaging the intestinal mucosa, affecting the absorption of nutrients, weakening the body's resistance, and then aggravating the intestinal mucosa.…”
Section: Discussionsupporting
confidence: 65%
“…A Salmonella Enteritidis (SE) é o patógeno entérico, pertencente à família Enterobacteriaceae, de origem alimentar, mais frequentemente distribuído na natureza em diferentes espécies animais e, em frangos de corte, pode resultar severas perdas econômicas, devido aos altos custos com erradicação e medidas de controle (1) . Ainda, de acordo com Andrade et al (2) , quando pintos neonatos estão contaminados com a Salmonella Enteritidis sofrem injurias intestinais, que pioram o desempenho das aves.…”
Section: Introductionunclassified